The Emergence of 5-Year-Olds’ Behavioral Difficulties: Analyzing Risk and Protective Pathways in the United Kingdom and Germany - Huang, Wei; Weinert, Sabine; Wareham, Helen; Law, James; Attig, Manja; von Maurice, Jutta; Roßbach, Hans-Günther (Frontiers in Psychology, 2022)
This study aimed to advance our understanding of 5-year-olds’ behavioral difficulties by modeling and testing both mediational protective and risk pathways simultaneously. Drawing on two national samples from different Western European countries—the UK (13,053) and Germany (2,022), the proposed model considered observed sensitive parental interactive behaviors and tested child vocabulary as protective pathways connecting parental education with children’s behavioral outcomes; the risk pathways focused on negative parental disciplinary practices linking (low) parental education, parental distress, and children’s difficult temperament to children’s behavioral difficulties. Further, the tested model controlled for families’ income as well as children’s sex and formal child care attendance. Children with comparatively higher educated parents experienced more sensitive interactive behavior, had more advanced vocabulary, and exhibited fewer behavioral difficulties. Children with a comparatively higher level of difficult temperament or with parents who suffered from distress tended to experience more negative disciplinary behavior and exhibited more behavioral difficulties. Additionally, children’s vocabulary skills served as a mechanism mediating the association between parental education and children’s behavioral difficulties. Overall, we found similar patterns of results across the UK and Germany with both protective and risk pathways contributing simultaneously to children’s behavioral development. The findings suggest that promoting parents’ sensitive interactive behaviors, favorable disciplinary practices, and child’s vocabulary skills have potential for preventing early behavioral difficulties.